The health related quality of life outcome of severe traumatic brain injury in two tertiary hospitals: a cohort study (ID: 008) - Mohamed Ludin, Salizar; Abdul Rashid, Nor'ain (2018)
Objective: Severe TBI survivors show physical and functional improvement, but remain with cognitive and psycho-social problem throughout recovery. Severe traumatic brain injury survivors show a low health related quality of life after injury. This study aim to measure the health related quality of life of severe traumatic brain injury survivors within 6 months post-injury. Method: A cohort study was conducted.33 severe TBI survivors were recruited at two tertiary hospitals. The health related quality of life were measured using the Quality of Life after Brain Injury tool. Results: The mean age of the participants were 31.79 years old. The result reported an impaired range of health related quality of life on 6 months post-injury, but an improvement occurs within 3 to 6 months post-injury. Conclusion: The quality of life after brain injury result revealed, age and duration on the ventilator showed a moderate negative correlation in all domains. Meanwhile, length of stay in hospital showed a moderate negative correlation to social, daily life and self domains. Nonetheless, a small sample size and time constraint were the limitations in this study.